Nutrient Stocks and Distribution in Ghanaian Cocoa Ecosystems - A. M. Mohammed; J. S. Robinson; A. Verhoef; D. J. Midmore (International Journal of Agronomy)
There is a paucity of information on nutrient stocks and distribution in the cocoa ecosystem for the management of production sites to improve its productivity. Apart, sites with long histories of cocoa production could differ in nutrient stocks and distribution relative to recent production regions. Therefore, some existing cocoa farms in Ghana were sampled on the basis of shade management (shaded and unshaded) and production site longevity (Eastern region > Western North region) to determine the nutrient stock and distributions in them. Over 93% of the total ecosystems’ elementary nutrients were stored in the soil. Higher nutrient stocks occurred under shaded cocoa ecosystem. Nutrient element concentrations in cocoa tree biomasses followed the order: N > Ca > K > Mg > P > S > Al = Fe > Zn = Mn, and mostly concentrated in leaf > root = husk > branch > stem. On average, region as a main factor affected nutrient distributions. There was a sharp distinction between macronutrient and micronutrient accumulations in favour of Eastern region and Western North region, respectively. Therefore, the regional distinction with respect to macro- and micronutrients could be used as a guide to fertilizer recommendation for cocoa systems in the two regions.